2013
DOI: 10.1002/ppap.201200089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Silver Nanoparticle Deposition onto Dielectric Barrier Discharge (DBD) Plasma Functionalized Polyamide Fabric

Abstract: The effect on the deposition of three different size silver nanoparticles (AgNPs) onto a polyamide 6,6 (PA) fabric pre‐treated using air dielectric barrier discharge (DBD) plasma was investigated. The SEM, EDS, and XPS analysis confirm that the smaller is the diameter of AgNPs, the higher the amount of adsorbed NPs on the PA. The DBD treatment on PA induces a threefold increase in Ag adsorption. The result confirms a dual effect on the wettability of the plasma treated PA substrate. AgNPs slightly enhance hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 71 publications
7
37
0
Order By: Relevance
“…[ 64] Results of agar disk diffusion tests to evaluate the antibacterial efficiency of the coatings are shown in Figure 9: while no growth inhibition area can be observed around the uncoated PE and pPAA coated PE samples, a clear zone with no bacterial growth can be clearly detected around the AgNPs/pPAA coated PE samples, similarly to what previously reported also by Sadeghnejad et al; [65] this behavior is indicative of the action Ag ions, probably released from Figure 6. XPS survey spectrum collected for the AgNPs/pPAA coating.…”
Section: Resultssupporting
confidence: 74%
“…[ 64] Results of agar disk diffusion tests to evaluate the antibacterial efficiency of the coatings are shown in Figure 9: while no growth inhibition area can be observed around the uncoated PE and pPAA coated PE samples, a clear zone with no bacterial growth can be clearly detected around the AgNPs/pPAA coated PE samples, similarly to what previously reported also by Sadeghnejad et al; [65] this behavior is indicative of the action Ag ions, probably released from Figure 6. XPS survey spectrum collected for the AgNPs/pPAA coating.…”
Section: Resultssupporting
confidence: 74%
“…Comprehensive investigations of functionalised textiles in the scientific literature have shown that textiles can be functionalised with well-defined NPs under laboratory conditions (Zhang et al, 2012;Nguyen Khanh et al, 2013). However, it is reasonable to assume that upscaling of functionalization methodologies to the industrial level may result in different outcomes from those achievable under well-controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, with an increase in nanoparticle size, the specific surface area and free energy decrease, which should lead to an increase in the contact angle. 9,42 However, several other factors such as surface charge, roughness, and nanoparticle distribution and mass concentration control the contact angle on a fibrous material surface. 43 In contrast to the contact angle, the surface free energy of the plasma-treated PA66 exhibited a certain dependency on the size of the deposited AgNPs.…”
Section: Deconvolution Analysis Of Xps Spectra At Day 30mentioning
confidence: 99%